PERBANDINGAN EFEKTIVITAS PEMBERIAN COKELAT HITAM DENGAN AROMATERAPI LEMON UNTUK MENGATASI NYERI HAID DI MADRASAH ALIYAH BANGUNTAPAN BANTUL YOGYAKARTA: Comparison Of Giving Dark Chocolate With Lemon Aromatherapy To Overcome Menstrual Pain In Madrasah Aliyah Banguntapan Bantul Yogyakarta - Murwani, Arita; Amry A, Riza Yulina; M, Ani Mashunatul; Ashar, Hadi (Jurusan Keperawatan, 2025)
ABSTRACT Background: The World Health Organization (WHO) in 2020 reported that the incidence of women experiencing severe dysmenorrhea in every country in the world is around 50% of the population and 10-15% of them experience mild dysmenorrhea. Greater prevalence is generally in young women, with estimates ranging from 67% to 90% for women aged 17-24 years. and in the Asian region cases of dysmenorrhea occur in 45-90% of women. Objective: To determine the comparison of giving dark chocolate with lemon aromatherapy to overcome menstrual pain in adolescent girls at MA Banguntapan Bantul Yogyakarta. Design: This study is an experimental study that examines the comparison of giving dark chocolate with lemon aromatherapy with pre-experimental. The sampling technique used accidental sampling, with a total of 30 respondents. before being given treatment or given an observation sheet (pretest) for respondents' menstrual pain. Then given dark chocolate and lemon aromatherapy and then followed by giving the second observation sheet (postest) to determine the respondent's menstrual pain scale after the therapy was given once with an interval of one week. Results: The results of the man whitney test obtained a p-value = 0.000 (p-value <0.005), with the results of the mean rank of dark chocolate intervention (39.88) and the mean rank of lemon aromatherapy intervention (21.12). Conclusion: there is a difference in the effect of dark chocolate intervention and lemon aromatherapy intervention. Suggestion: The provision of lemon and dark chocolate aromatherapy is expected to be included in the management program on how to deal with menstrual pain because it is able to reduce menstrual pain in adolescent girls at MA Banguntapan Bantul Yogyakarta. Keywords: Menstrual Pain, Lemon Aromatherapy, Dark Chocolate